Chitosan Antibacterial Of Portunus Pelagicus Against Biofilm Porphyromonas Gingivalis - Laurencia Isabella Loekito; Yoifah Rizka; Fani Pangabdian (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2018)
Background: Porphyromonas gingivalis bacteria are found in dental plaques and have the ability to form biofilms. Biofilms are collections of bacterial cells, which are tightly attached to a surface covered by an extracellular polymer matrix released by the bacteria. Periodontitis therapy generally uses tetracycline antibiotics which if used long-term can cause resistance. Chitosan Rajungan crab extract (Portunus pelagicus) has antimicrobial potential which can be used as an alternative therapy. Objective: To determine the antibacterial power of Rajungan crab chitosan extract (Portunus pelagicus) in various concentrations of Porphyromonas gingivalis bacterial biofilms. Method: This research was true experimental laboratorist. This study used Rajungan crab chitosan extract (Portunus pelagicus) to Porphyromonas gingivalis biofilm tested by the test method biofilm. Divided into 5 groups, where each group consisted of 4 samples. The control group consisted of: K- (negative control group), K + (positive control group / tetracycline group), and 3 treatment groups, namely P1 (0.25% Rajungan crab chitosan), P2 (0.5% Rajungan crab chitosan) , P3 (1% Rajungan crab chitosan). Antibacterial power was determined by the value of Optical density in the ELISA Reader. Data analysis using One Way ANOVA followed by LSD test. Result: There were significant differences (p <0.05) seen from the percentage of biofilm inhibition in the negative control group for all groups, the positive control group for the crab crab chitosan extract concentrations of 0.25% and 0.5%. Conclusion: The chitosan crab chitosan extract (Portunus pelagicus) with 1% concentration has the greatest antibacterial effect on the Porphyromonas gingivalis biofilm.